Systematic literature review on effectiveness of self‐management support interventions in patients with chronic conditions and low socio‐economic status. (20th October 2016) - Van Hecke, Ann; Heinen, Maud; Fernández‐Ortega, Paz; Graue, Marit; Hendriks, Jeroen M.L.; Høy, Bente; Köpke, Sascha; Lithner, Maria; Van Gaal, Betsie G.I.
Abstract: Aim: To assess the quality of evidence and determine the effect of patient‐related and economic outcomes of self‐management support interventions in chronically ill patients with a low socio‐economic status. Background: Integrated evidence on self‐management support interventions in chronically ill people with low socio‐economic status is lacking. Design: Systematic literature review. Data sources: Cochrane database of trials, PubMed, CINAHL, Web of Science, PsycINFO and Joanna Briggs Institute Library were searched (2000–2013). Randomized controlled trials addressing self‐management support interventions for patients with cardiovascular disease, stroke, cancer, diabetes and/or chronic respiratory disease were included. Review methods: Data extraction and quality assessment were performed by independent researchers using a data extraction form. Results: Studies ( n = 27) focused mainly on diabetes. Fourteen studies cited an underlying theoretical basis. Most frequently used self‐management support components were lifestyle advice, information provision and symptom management. Problem‐solving and goal‐setting strategies were frequently integrated. Eleven studies adapted interventions to the needs of patients with a low socio‐economic status. No differences were found for interventions developed based on health behaviour theoretical models. Conclusion: Limited evidence was found for self‐management support interventions in chronically ill patients with low socio‐economic status. Essential characteristics and component(s) of effective self‐management support interventions for these patients could not be detected. Rigorous reporting on development and underlying theories in the intervention is recommended.